Shoulder strength and range of motion in symptomatic and pain-free elite swimmers - Bak, K.; Magnusson, S. P. (The American Journal of Sports Medicine, 1997)
To evaluate differences in shoulder strength and range of motion between painful and pain-free shoulders we examined two matched groups of athletes. Fifteen competitive swimmers were allocated to two groups. Group 1 consisted of seven swimmers with unilateral shoulder pain related to swimming (Neer and Welsh phase I to II). The control group (Group 2) consisted of eight swimmers with no present or previous history of shoulder pain. Concentric and eccentric internal rotational torques were reduced in painful shoulders in between-group comparisons as well as in side-to-side comparisons. The decrease in internal rotational torque resulted in significantly greater concentric and eccentric external-to-internal rotational strength ratios of the painful shoulder in Group 1 swimmers compared with the controls. Furthermore, the functional ratio (eccentric external rotation:concentric internal rotation) was significantly greater in the painful shoulder in both between-group and side-to-side comparisons. Both groups of swimmers exhibited increased external range of motion and reduced internal range of motion compared with normalized data, but no between-group or side-to-side differences were detected. Our findings suggest that prevention or rehabilitation of swimmer's shoulder might not solely involve strengthening of the external rotators of the shoulder joint. Attention might also be drawn toward correction of a possible deficit in internal rotational strength. Changes in shoulder range of motion seem unrelated to the occurrence of shoulder pain.